Sex Disparity in Severity of Lung Lesions in Newly Identified Tuberculosis Is Age-Associated - Chu, Yue; Soodeen-Lalloo, Adiilah K.; Huang, Jin; Yang, Guanghong; Chen, Fengfang; Yin, Hongyun; Sha, Wei; Huang, Xiaochen; Shi, Jingyun; Feng, Yonghong (Frontiers in Medicine, 2019)
Background: The age-associated characteristic of computed tomography (CT) images of tuberculosis (TB) and the reason for male bias in TB is still not clear. Methods: We compared the CT images, clinical inflammatory indices and sputum bacterial counts between 594 non-smoking men and women with newly diagnosed TB, with matched large span of ages from 15 to 92 years old. Logistic regression analyses were used to identify the cavity-associated factors in of men and women, separately and in combination. Results: Sputum bacterial counts, ratio of cavities, lung injury scores, and level of C reactive protein were significantly higher in men than in women with ages from 15 to 74, but not in cases older than 75. In CT images, thick walled cavity, cicatricial emphysema and parenchymal bands were more in men at ages of 15-74 than matched women. Ratios of cases with lobular emphysema and pleural effusion were higher in men after age of 56. While ratios of cases with parenchymal bands, calcification, pleural effusion, pleural thickening, lobular emphysema and bronchiovascular distortion increased with aging, those of centrilobular nodules, micronodules, and tree in bud decreased with aging in men. Erythrocyte sedimentation rate (ESR) increased with aging, but no differences were found between men and women in ESR and in T-SPOT TB test. Higher complement C4 and lower body mass index in men and positive result in anti-TB antibody test in women were strongly associated with cavity. Conclusions: The sex bias in TB is age-associated. TB prevention , treatment and research should take the difference of sex and age into account.